MENTAL ILNESS PADA REMAJA DAN PERAN AGAMA DALAM MEMBENTUK KESEHATAN MENTAL - Akhmad Khairi; Surawan Surawan (CV. Adiba Aisha Amira, 2025)
Mental health is the foundation of emotions, thoughts, communication, learning, resilience, hope, and self-esteem. It also plays an important role in interpersonal relationships, personal and emotional well-being, and contributions to society. Mental disorders, often referred to as mental illnesses, are mild mental health problems that affect thoughts, feelings, behaviour, mood, or a combination of all of these. Religion plays a very important role in maintaining a person's mental health. This study will examine how religion can contribute to shaping the mental health of adolescents to prevent mental disorders. The method used in this study is a literature study, in which the researcher will collect information from various sources such as books, journals, articles, magazines, newspapers, and other media to support the discussion. For a more in-depth analysis, a descriptive method will be applied to make the discussion clearer.